Government to request extradition of Abu Marzook: Daily Edition - Makovsky, David; Henry, Marilyn; and news agencies (The Jerusalem post, 1995)
THE government decided last night to ask the US to extradite Mousa Abu Marzook, whom Israeli officials have called Hamas's "foreign minister," according to an official who attended the deliberations at the Prime Minister's Office. The government had to make a quick decision on the extradition of Abu Marzook, who was apprehended last week by US immigration authorities at New York's John F. Kennedy Airport. Failure to decide to extradite now would mean that the US could simply decide to deport him back to Abu Dhabi this week. The US generally expels people back to where they began their journey to America. It is crucial to both the US and Israel that there is rock-solid evidence against Abu Marzook, so extradition can withstand the inevitable legal challenges in the US and a conviction can be obtained in Israel.